A Review: Diagnosis and Treatment of Monkeypox Patients: Sebuah Tinjauan: Diagnosis dan Pengobatan Pasien Cacar Monyet - Hussein, Salwa Hamza; Dakil, ZainabAbd al-azim; Nasser, Batheena Abed alhassan (Universitas Muhammadiyah Sidoarjo, 2024)
A viral illness impacting children and young adults, it commences gradually and the infection can be minor. A significant proportion of patients progress to the acute stage of the infection. The condition progresses in the acute phase to encephalitis, myocarditis, pneumonia, and ocular complications in severe instances. The monkeypox viral infection constitutes a significant global public health issue. The nation carries the highest burden of monkeypox infections internationally and will significantly contribute to the eradication of this disease worldwide. Despite the country's significant advancements in mitigating monkeypox virus infections in prior years, Iraq currently encounters obstacles in its objective to diminish the fatality and morbidity rates associated with monkeypox. In alignment with the WHO global health sector policy on monkeypox, we emphasise additional priority for action to eradicate this virus in Iraq, aiming to accomplish the objective of lowering death, and we recommend prioritising service coverage targets for diagnosis and treatment. Initially, it is essential to enhance the diagnostic and therapeutic capabilities of medical facilities and healthcare professionals. Secondly, the government must alleviate the financial strain of healthcare on patients. Third, improved coordination of current national initiatives and resources is essential to create an integrated prevention and control system encompassing the prevention, screening, diagnosis, and treatment of HIV infection and monkeypox across the life cycle. Thus, advancement can be achieved in the objective of eradicating monkeypox in Iraq. Highlights: Gradual onset illness affecting children, causing severe complications in acute stage. Iraq faces challenges in reducing monkeypox fatality and morbidity rates. Focus: Enhance healthcare, ease costs, and improve prevention coordination. Keywords: Mpox, Health problem, Infection, Diagnosis and treatment.